Desempenho ao ruído de impacto de laje pré-fabricada nervurada de vigotas protendidas e lajotas cerâmicas com revestimento de pisos laminados - Lourenço, Willian Magalhães de (2020)
The advancement of new technologies has resulted in civil construction in the verticalization of cities in buildings, corroborating to a demand for requirements arising from performance standards and also from users, thus, architectural acoustics is one of the parameters to be considered in the face of such issues. Faced with the elucidated problems, the Brazilian Association of Technical Standards elaborated the NBR 15575 (Housing Buildings - Performance) to guarantee the users minimum performance of habitability, one of them is the acoustic performance. This research uses impact noise tests in accordance with ISO 16283-2: 2018 and ISO 717-2: 2013 to determine the sound pressure level of weighted standard impact (L'nT,w), in floor systems with prefabricated ribbed slab of prestressed joists and ceramic tiles with laminated wooden flooring, and with the aid of resilient materials adopting the constructive technique called floating floor, totaling 39 different sample compositions. The results show that the bone slab and the slab and subfloor system do not meet the minimum acoustic performance requirements established by the standard, with values of 91 dB and 84 dB respectively. Among the other 37 samples, it is noteworthy that AC3 laminate floors have better performances compared to AC4 floors, with values from 60 dB to 62 dB. For samples using resilient materials, performance values range from 55 dB to 48 dB, the best results being from samples using 10 mm polyester wool and 15 mm glass wool. Therefore, prefabricated slabs that have lower mass require the use of floating floors for better acoustic performance in buildings for impact noise. This research aims to contribute to the knowledge of various materials regarding architectural acoustics, and corroborates for better living conditions, design and executive efficiency in the construction sector.